2019
DOI: 10.1016/j.watres.2018.10.047
|View full text |Cite
|
Sign up to set email alerts
|

Metalimnetic oxygen minimum and the presence of Planktothrix rubescens in a low-nutrient drinking water reservoir

Abstract: Dissolved oxygen is a key player in water quality. Stratified water bodies show distinct vertical patterns of oxygen concentration, which can originate from physical, chemical or biological processes. We observed a pronounced metalimnetic oxygen minimum in the low-nutrient Rappbode Reservoir, Germany. Contrary to the situation in the hypolimnion, measurements of lateral gradients excluded the sediment contact zone from the major sources of oxygen depletion for the metalimnetic oxygen minimum. Instead, the mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 51 publications
3
32
0
Order By: Relevance
“…Both in Arendsee and Rappbode Reservoir, a reduction of oxygen concentrations could be measured: both lakes formed a metalimnetic oxygen minimum. This could possibly be attributed to the decomposition of organic material below the epilimnion, while the metalimnetic and hypolimnetic water remained disconnected from the supply with new oxygen from the atmosphere (see also [54,55] for Rappbode Reservoir; [56,57] for Arendsee).…”
Section: General Picture Of Circulation and Atmospheric Rechargementioning
confidence: 99%
“…Both in Arendsee and Rappbode Reservoir, a reduction of oxygen concentrations could be measured: both lakes formed a metalimnetic oxygen minimum. This could possibly be attributed to the decomposition of organic material below the epilimnion, while the metalimnetic and hypolimnetic water remained disconnected from the supply with new oxygen from the atmosphere (see also [54,55] for Rappbode Reservoir; [56,57] for Arendsee).…”
Section: General Picture Of Circulation and Atmospheric Rechargementioning
confidence: 99%
“…The outlets are discharging either into the downstream river Bode towards Wendefurth Reservoir (gauge Hirtenstieg) or into a water transfer gallery towards Rappbode Reservoir. The water gallery delivers approximately one third of the annual inflow into Rappbode Reservoir, which is the largest drinking water reservoir in Germany in terms of volume, providing drinking water to more than one million people (Wentzky et al 2018a).…”
Section: Study Sitementioning
confidence: 99%
“…Effler et al have introduced the characteristics and origin of MOM in an eutrophic reservoir in New York, and found that MOM is a recurring phenomenon due to the respiration of relatively high concentrations of phytoplankton biomass within the metalimnion [10]. Wentzyk et al also reported the MOM phenomenon in Rappbode Reservoir located in the Harz Mountains in Northern Germany, and found that the respiration of phycoerythrin-rich Planktothrix rubescens was responsible for the oxygen minimum in metalimnion in a low-nutrient drinking water reservoir [15]. Kreling et al further revealed the function of physical transport and oxygen consumption for the development of MOM in a lake, which concluded that more DO was consumed in the metalimnion than that transported to this layer at the same time [16].…”
Section: Introductionmentioning
confidence: 99%
“…Kreling et al further revealed the function of physical transport and oxygen consumption for the development of MOM in a lake, which concluded that more DO was consumed in the metalimnion than that transported to this layer at the same time [16]. The previous studies have preliminarily summarized the formation of MOM mainly due to the following reasons: (1) Higher DO consumption in the metalimnion was mainly attributed to the enhanced decomposition of dead algae or respiration of algae beyond their photosynthetic activity in the metalimnion [15]; (2) the interflow of DO depleted or depleting water also has been claimed to be an important influencing factor for MOM formation [17]; (3) MOM has been related to oxygen depletion at the side wall in some situation, which was advected into the water body of the reservoir on isopycnal water layer [18]; (4) finally, vertical gradient in the water column due to the retardation of diapycnal transfer and vertical exchange led to the reoxygenation difficulty [19]. Although those studies have reported MOM phenomenon in different areas and stated the reasons, the characteristics including the MOM formation mechanisms, the developed thickness and ecological risk of this phenomenon in reservoirs are of great difference with regard to hydrological and climatic conditions [10,15,20,21,22,23].…”
Section: Introductionmentioning
confidence: 99%